TANGGUNG JAWAB PELAKU USAHA TERHADAP APARTEMEN YANG TIDAK MEMENUHI SYARAT SERTIFIKAT LAIK FUNGSI MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI PUTUSAN NOMOR 553/Pdt.G/2016/PN.JKT.UTR) - Monica Hendrawan; Sri Bakti Yunari (Fakultas Hukum Universitas Tarumanagara, 2020)
Apartment are one of many options that peoples choose to live in especially for peoples that live in capital city such as Jakarta. In the process construction of apartements, there are one requirements that must be completed, one of them is the Building Worthiness Certificate. Building Worthiness Certificate is a certifivate that issued by the regional government. In fact, there are still many apartements in Jakarta that didn’t fullfied the requirements, Robinson Apartment which was build by PT Putra Mas Simpati is one of them. How is the responsibility of developer that didn’t fullfied the Building Worthiness Certificate requirement in the construction of Robinson Apartment and what are the legal consequences for developer that don’t have Building Worthiness Certificate (Contractual Liability). According to Law Number 9 of 1999 concerning Consumer Protection Article 28, developer should be liable for damages, however the compensation given is based o the decision of the Court Number 553/Pdt.G/2016/JKT.UTR apparently are not fulfilling or suitable. While to the law about Building Worthiness Certificate which is not fulfilled in the construction of Robinson Apartment by PT Putra Mas Simpati, according toLaw Number 20 of 2011 concerning Flats Article 107-108, developer may be subject to administrative sanctions. As a suggestion, more intensive guidance and supervision are needed for businesses that build apartment from the Regional Government and the Ministry of Public Works and Public Housing.